Empty Sella Syndrome in a Postmenopausal Woman (BIRDEM Medical Journal, 2012)
A 50-year-old, prematurely postmenopausal diabetic woman was admitted in the Endocrinology department of BIRDEM with the complaints of vomiting, loose motion, lethargy, profound weakness. Previously she suffered from several episodes of electrolyte imbalance and after investigations adrenal insufficiency was diagnosed on 2010. No evaluation was done for her premature menopause. During this episode of illness, she was found with postural hypotension, hyponatremia, dyslipidemia and panhypopituitarism. MRI of sella and parasellar region was done which revealed features suggestive of empty sella. This case gives insight that early menopause warrants proper evaluation and during evaluation, along with other factors hypopituitarism should be considered as an etiology for this condition. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12362 Birdem Med J 2012; 2(1) 52-55